Development of Interactive Science Learning Video Based on Ethnoedutour in Muaro Jambi Temple Area - Jufrida; M. Furqon; Rahma Dani; Hebat Shidow Falah; M. Haykal Alfaizi (Postgraduate, University of Mataram, 2024)
This study aims to develop an interactive science learning video based on ethnoedutour on pressure material for junior high school students by integrating local wisdom from the Muaro Jambi Temple Area. The research method used is Research and Development (R&D) with the ADDIE model, as well as a mixed methods approach using exploratory sequential design. This research was conducted through three stages, namely analysis, design, and development. The analysis stage involved observations, interviews, and questionnaires to identify learning needs and learner characteristics. At the design stage, the video structure and storyboard were prepared based on the results of the analysis, while the development stage involved product validation by experts and student testing. The validation results show that this interactive learning video media is suitable for use, with significant improvements in the material and media aspects. The trial of 25 students showed a positive response with an average score above 80% on the aspects of material, feedback, motivation, ease of use, interaction, and accessibility. This study concludes that the interactive learning video based on *ethnoedutour* is effective in helping students understand pressure material through the local cultural context. However, further research is needed to evaluate the effectiveness of the product in increasing students' learning motivation as well as in the implementation and evaluation stages.